Successful Intra-Arterial Chemotherapy for Extramammary Paget’s Disease of the Axilla in a Patient with Parkinson’s Disease - Damascelli, Bruno; Ticha, Vladimira (CardioVascular and Interventional Radiology, 2011)
Extramammary Paget’s disease (EMPD) is a rare intraepithelial neoplasm occurring less frequently in men and even more rarely in the axilla. A 59-year-old man with severe Parkinson’s disease presented with axillary EMPD. The neurological comorbidity made treatment of the EMPD problematical and prompted us to propose locoregional intra-arterial chemotherapy in single short sessions. Two innovative chemotherapeutic macrocomplexes were used: doxorubicin incorporated in large liposomes and the taxane paclitaxel incorporated in albumin nanoparticles. A therapeutic response was seen right from the first treatment and was macroscopically close to complete after four cycles. Five months after the end of treatment the patient had minimal visible disease and had enjoyed a distinct improvement in quality of life, with no noteworthy complications related to the intra-arterial chemotherapy with percutaneous transfemoral catheterization.